Surgical and anatomic factors predict development of leptomeningeal disease in patients with melanoma brain metastases. Issue 8 (29th January 2022) - Lowe, Stephen R; Wang, Christopher P; Brisco, Amanda; Whiting, Junmin; Arrington, John; Ahmed, Kamran; Yu, Michael; Robinson, Timothy; Oliver, Daniel; Etame, Arnold; Tran, Nam; Beer Furlan, Andre; et al.
Abstract: Background: Leptomeningeal disease (LMD) is a devastating complication of systemic malignancy, of which there is an unclear etiology. The aim of this study is to determine if surgical or anatomic factors can predict LMD in patients with metastatic melanoma. Methods: A retrospective chart review was performed of 1162 patients treated at single institution for melanoma brain metastases (MBM). Patients with fewer than 3 months follow-up or lacking appropriate imaging were excluded. Demographic information, surgical, and anatomic data were collected. Results: Eight hundred and twenty-seven patients were included in the final review. On multivariate analysis for the entire cohort, female gender, dural-based and intraventricular metastasis, and tumor bordering CSF spaces were associated with increased risk of LMD. Surgical resection was not significant for risk of LMD. On multivariate analysis of patients who have undergone surgical resection of a metastatic tumor, dural-based and intraventricular metastasis, ventricular entry during surgery, and metastasis in the infratentorial space were associated with increased risk of LMD. On multivariate analysis of patients who did not undergo surgery, chemotherapy after initial diagnosis and metastasis bordering CSF spaces were associated with increased risk of LMD. Conclusion: In a single-institution cohort of MBM, we found that surgical resection alone did not result in an increased risk of LMD. Anatomical factors such as dural-based and intraventricular metastasis were significant for developing LMD, as well as entry into a CSF space during surgical resection. These data suggest a strong correlation between anatomic location and tumor cell seeding in relation to the development of LMD.